Harmful Socio-Cultural Practices and Gendered Oppression in Northern Nigeria: A Phenomenological Study - Uroko, Favour (The Faculty of Ushuluddin and Humanities, Universitas Islam Negeri Walisongo Semarang, Indonesia, 2025)
In Northern Nigeria, deeply embedded socio-cultural and religious norms continue to marginalize girls and young women through systemic practices such as child marriage, sexual violence, limited access to reproductive health education, and economic dependency. Despite increasing awareness of gender inequality in the region, there remains a limited understanding of the lived experiences of affected individuals. This study explores how patriarchal values and harmful traditions shape the daily realities of girls and women in northeastern and northwestern Nigeria. Using a qualitative phenomenological approach, data were collected through in-depth oral interviews with 30 purposively selected participants aged 12–73. Thematic analysis using the Colaizzi method revealed four major themes: widespread sexual abuse, unsafe abortion practices, limited health literacy, and deepening economic dependence. These findings highlight how silence—driven by cultural taboos and institutional neglect—perpetuates gender-based harm. The study contributes to global gender discourse by foregrounding the voices of marginalized Muslim girls and women, offering culturally contextualized evidence to inform gender-sensitive policy and advocacy by governments, NGOs, and faith-based organizations.